ANALYSIS OF SPEECH FUNCTION IN THE 2024 INDONESIAN PRESIDENTIAL DEBATE - Soegiarto, Herryono; Supatmiwati, Diah; Sudewi, Ni Ketut Putri Nila; Muhid, Abdul; Syamsurrijal, Syamsurrijal (Universitas PGRI Sumatera Barat, 2025)
This study is about the speech function used in the 2024 Indonesian presidential candidate debates. The purpose of this study is to find out the types and the meaning of speech function and to differentiate and similarities in the speech function in Indonesian 2024 presidential candidate debates based on Halliday (2024) classification of speech function. Qualitative research design is used to analyze the data. This research analyzed speech functions in the fifth Indonesian presidential election debate held on February 4, 2024. Data were sourced from KompasTV Sukabumi’s official YouTube channel and underwent data condensation before analysis. A total of 84 clauses were analyzed, with Anies Baswedan producing 36, while Prabowo Subianto and Ganjar Pranowo each uttered 24. The result showed 84 utterances identified as speech function. The number of speeches delivered by candidate Anies Baswedan’s was 36 utterances, Prabowo Subianto’s was 24 utterances, and Ganjar Pranowo’s was 24 utterances. The most frequently used speech functions are Statement, Offer, Question, and Command.